2008
DOI: 10.1080/03008200802148355
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 and Transforming Growth Factor-ß 1 as Crucial Factors in Osteoarthritic Cartilage Metabolism

Abstract: In osteoarthritis (OA), interleukin-1 (IL-1) stimulates the expression of metalloproteinases and aggrecanases, which induce cartilage degradation. IL-1 is also capable of reducing the production of cartilage-specific macromolecules, including type II collagen, through modulation of the transcription factors Sp1 and Sp3. Conversely, Transforming growth factor-beta (TGF-beta) counteracts with most of the IL-1 deleterious effects and contributes to cartilage homeostasis. However, OA chondrocytes progressively loo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
99
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 44 publications
3
99
0
3
Order By: Relevance
“…cartilage degradation, in part via its ability to stimulate the expression of metalloproteinases and reduce cartilage-specific molecules, such as type II collagen (2). IL-1␤ also stimulates prostaglandin E 2 (PGE 2 ) production by up-regulation of cyclooxygenase 2 (COX-2), which may worsen symptoms of OA (3,4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…cartilage degradation, in part via its ability to stimulate the expression of metalloproteinases and reduce cartilage-specific molecules, such as type II collagen (2). IL-1␤ also stimulates prostaglandin E 2 (PGE 2 ) production by up-regulation of cyclooxygenase 2 (COX-2), which may worsen symptoms of OA (3,4).…”
mentioning
confidence: 99%
“…Our data also support the view that ERR␣ plays a role in cartilage homeostasis and may also play complex and multifactorial roles in the response of OA chondrocytes. Indeed, the fact that ERR␣ expression is up-regulated by the proinflammatory mediators IL-1␤ and PGE 2 , but not by HGF and TGF␤, the latter being associated with mild cartilage remodeling, suggests that ERR␣ plays a role in cartilage degradation (2,27). IL-1␤ is a proinflammatory cytokine produced endogenously not only by articular chondrocytes (28), but also by the synovial membrane in OA (29).…”
mentioning
confidence: 99%
“…3) Many researches have also demonstrated that enzymatic cleavage by matrix metalloproteinases (MMPs) together with cytokines plays critical roles in the initiation and progression of cartilage destruction. 4,5) An imbalance between MMPs and tissue inhibitors of metalloproteinases (TIMPs) is an determinant of the extent of ECM turnover. 6) Hence, a therapeutic approach regulating the MMPs/TIMPs balance and apoptosis may be eŠective in the treatment of OA.…”
Section: Introductionmentioning
confidence: 99%
“…5) It is always used on cartilage and chondrocyte to establish an OA model. 13,14) Thus, in the present study, we investigated the potential of SIN to protect rabbit cartilage and chondrocytes against imbalance of MMP-13/TIMP-1 and apoptosis in an IL-1b-mediated OA model.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is the most common form of arthritis in humans and a leading cause of disability worldwide, its complex pathogenesis remains poorly understood and no disease-modifying drug is currently available (1,2). Synovial inflammation has been implicated in the development of OA, and the proinflammatory cytokine IL-1β has been identified as one of the key mediators produced by activated synovial macrophages to promote the inflammatory and destructive responses in OA (3,4). The level of IL-1β is elevated in synovial fluids and the cartilage of OA patients (5).…”
mentioning
confidence: 99%